The Analysis of Emoji as Social Identity Markers as Found in NCT KPOP Fan Twitter Usernames - Zhafira, Ulfa; Ayumi, Ayumi (LingoLitera, 2026)
This research aims to analyze how emojis are used in digital communication, particularly in usernames, to represent social identity within the Kpop Idol, NCT Dream fandom (NCTzens). The study focused on usernames found in the comment section of the official NCT Dream Twitter account during the fans meeting <Dream Quest> with NCTzens Day 1 on May 24, 2025, at 10:00 PM. The study applied Computer-Mediated Discourse Analysis (CMDA) by Susan C. Herring (2004) as the main theoretical framework, supported by Social Identity by Tajfel and Turner (1979) and the Indexicality Theory by Buncholtz and Hall (2005) which analysis examines how emojis relate to identity. The data consisted of 88 usernames containing emojis, which were analyzed to identify which emojis functioned as social identity markers and which served just as decorative elements. The findings reveal that emojis in usernames have dual functions, first they as a social identity marker, indexing fandom identity, symbolic attachment to NCT Dream and associations with specific members, and second is as decorative elements, used for aesthetic enhancement without identify significance. The study identifies 10 types of emojis in usernames account distributed across animal, nature, and activity. In conclusion, this study shows that the use of emojis in usernames within the NCT Dream fan community reflects both sociolinguistic identity construction and aesthetic expression. Emojis therefore play a significant role as linguistic features in computer-mediated communication, shaping how online fan communities display belonging, identity, and symbolic meaning.